2015
DOI: 10.2174/1570159x13666150630173522
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Treatment-Resistant Major Depressive Disorder: A Roadmap for Improved Therapeutics

Abstract: Major depressive disorder (MDD) is associated with a significant burden and costs to the society. As remission of depressive symptoms is achieved in only one-third of the MDD patients after the first antidepressant trial, unsuccessful treatments contribute largely to the observed suffering and social costs of MDD. The present article provides a summary of the therapeutic strategies that have been tested for treatment-resistant depression (TRD). A computerized search on MedLine/PubMed database from 1975 to Sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 170 publications
1
32
0
1
Order By: Relevance
“…This suggests that cholesterol, particularly in the prefrontal cortex, influences the sensitivity of the 5-HT1A receptor in the pathology and treatment of depression. However, the serotonergic explanation of depression is not sufficient to fully explain the development of depression, as evidenced by large proportion of patients that do not respond to antidepressants which target the serotoninergic system [11,75,76]. …”
Section: Cholesterolmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that cholesterol, particularly in the prefrontal cortex, influences the sensitivity of the 5-HT1A receptor in the pathology and treatment of depression. However, the serotonergic explanation of depression is not sufficient to fully explain the development of depression, as evidenced by large proportion of patients that do not respond to antidepressants which target the serotoninergic system [11,75,76]. …”
Section: Cholesterolmentioning
confidence: 99%
“…Whilst these aim to reduce subjectivity and inter-clinician variability, they are arguably inadequate to provide a complete assessment and appropriate treatment plan [10]. In addition to inadequacies in diagnosis, up to 30% of patients do not respond to antidepressant medication and are diagnosed as having treatment-resistant depression [11]. Those that do exhibit a response often only receive a partial reduction in symptoms and a large proportion of the apparent efficacy of antidepressants has been proposed to be due to the placebo effect [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, tolerance to antidepressants has been reported [36]. Patients with TRD also had more complex treatment regimens, since it is a common strategy to use higher doses and adjunctive psychotropics to counter poor response to medication [37]. A recent meta-analysis of placebo-controlled trials demonstrated that adjunctive antipsychotics were effective for the treatment of TRD [38].…”
Section: Discussionmentioning
confidence: 99%
“…B. 30 % bei Depressionen [7]) kann allerdings als Indiz dafür gelten, dass die überwiegend psychopathologisch abgeleiteten Diagnosezuordnungen (s. o. ) mit den biologischen Wirkkategorien der Psychopharmaka unzureichend übereinstimmen.…”
Section: Warum Biobanking In Der Psychiatrie? Besonderheiten In Der Punclassified